2016
DOI: 10.1111/1744-7917.12402
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and biogeography of a species‐rich ant fauna of the Australian seasonal tropics

Abstract: Although ants are an ecologically dominant and extensively studied faunal group throughout the tropics, there is a poor understanding of tropical ant diversity and distribution at large spatial scales. Here we use a collection developed from 3 decades of ant surveys to present the first analysis of ant diversity and biogeography of a large tropical region. Our objective was to document the species richness, composition, and biogeographic distributions of the ant fauna of the 400 000 km "Top End" of Australia's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
0
18
0
1
Order By: Relevance
“…By way of comparison, a recent CO1 analysis of the ant fauna of Brazil's southern Atlantic Forest indicated that species richness was only 10% higher than previously appreciated [85], rather than the several-fold increase that is apparent for the AMT. Our findings call for a re-evaluation of the recent assessment based on the TERC collection that 900 species are known from the Top End of the Northern Territory [40]. Since this assessment, an extensive survey of remote areas of Kakadu and Nitmiluk National Parks have revealed >100 additional species (Oberprieler and Andersen unpubl.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…By way of comparison, a recent CO1 analysis of the ant fauna of Brazil's southern Atlantic Forest indicated that species richness was only 10% higher than previously appreciated [85], rather than the several-fold increase that is apparent for the AMT. Our findings call for a re-evaluation of the recent assessment based on the TERC collection that 900 species are known from the Top End of the Northern Territory [40]. Since this assessment, an extensive survey of remote areas of Kakadu and Nitmiluk National Parks have revealed >100 additional species (Oberprieler and Andersen unpubl.…”
Section: Discussionmentioning
confidence: 78%
“…Based on specimens in the Commonwealth Scientific Industrial Research Organisation (CSIRO) Tropical Ecosystems Research Centre's (TERC) ant collection in Darwin, there appears to be at least 26 valid species, one of which (Papyrius sp. 1) seemingly occurs throughout the AMT [40,41] and is one of our target species (Figure 2A). Syntypes of P. nitidus queenslandica are from Mackay on the central Queensland (Qld) coast, and Papyrius sp.…”
Section: Study Taxa and Co1 Barcodingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most ant species in northern Australia are undescribed and these were identified to species‐group following Andersen () and assigned code numbers that have been used in previous studies of ants in the region (e.g. Andersen et al ; Oberprieler et al ).…”
Section: Methodsmentioning
confidence: 99%
“…Wetterer (2014) lists several islands in the Lesser Antilles (Barbados, St. Lucia, Grenada, Anguilla, St. Martin, St. Kitts, Nevis, Guadeloupe, and Martinique) and in Bermuda (Wetterer 2017) as occupied by P. alluaudi. A few additional invasive establishments of P. alluaudi include Capricorna Cays, Australia (Hoffmann & Kay 2009); 'Top End', Northwest Territory, Australia (Andersen et al 2016); and Nansei Islands, Japan (Harada et al 2015).…”
Section: Establishment Of Alluaud's Little Yellow Ant Plagiolepis Almentioning
confidence: 99%